Investigating the role of Rab GTPases in medulloblastoma pathogenesis - Entwistle, Susannah J. (2024)
Introduction: Medulloblastoma is the most common malignant paediatric brain cancer, accounting for 20% of paediatric brain tumours and 10% of all cancer deaths. It is located within the cerebellum and is defined by four molecular subgroups: Wingless (WNT), Sonic Hedgehog (SHH), group 3 and group 4. Whilst WNT and SHH are named after the pathways which drive these tumours, the mechanisms underlying groups 3 and 4 are less well understood. Group 3 tumours are the group most likely to be metastatic at diagnosis and are therefore associated with the poorest prognosis. There is therefore a particular need to investigate the mechanisms that drive these tumours, to enhance diagnostic methods and treatment strategies and eventually improve patient outcomes. Exosomes are small membrane-bound extracellular vesicles (EV) of endosomal origin. They contain a variety of cargo, including RNA and proteins. Increased exosome release has been associated with disease progression and metastasis in multiple cancers. Rab GTPases (Rabs) are a family of small GTPases (66 in humans) which regulate vesicle trafficking. Several Rabs have been shown to regulate exosome biogenesis and secretion and may consequently contribute to cancer progression. Rabs also have non-exosomal associations with tumourigenesis through roles in intracellular vesicular trafficking. The role of Rabs in medulloblastoma pathogenesis has not yet been investigated. This study aims to therefore explore the pathways in which Rabs may contribute to medulloblastoma pathogenesis.